Structure of human Rack1 protein at a resolution of 2.45 Å - Lescar, Julien (2013)
The crystal structure of human receptor for activated C-kinase 1 (hRack1) protein is reported at 2.45 Å resolution. The crystals belongs to space group P41212, with three molecules per asymmetric unit. The hRack1 structure features a sevenfold -propeller, with each blade housing a sequence motif that contains a strictly conserved Trp, the indole group of which is embedded between adjacent blades. In blades 1-5 the imidazole group of a His residue is wedged between the side chains of a Ser residue and an Asp residue through two hydrogen bonds. The hRack1 crystal structure forms a starting basis for understanding the remarkable scaffolding properties of this protein.